Um estudo sobre a qualidade do ar de Uberlândia : material particulado em suspensão - Lima, Euclides Antônio Pereira de (2007)
The city of Uberlândia is one of the most populous of Minas Gerais State, and has the second greatest fleet of motor-vehicles of the State. The motor-vehicles are responsible for a great amount of pollutants emitted to the atmosphere. The vehicular pollution added to the diverse sources of existing pollutants, including from industries, speeds up the concern with possible damages to human health and to environment, came from the aggrievement of this problem. By the period of 2003 to 2006, samplings of particle material in suspension were made using great volume samplers, in order to collect total particles (PTS), inhalable particles (MP10), and a sampler of small volumes collecting even more fine particles (MP2,5). The work envisioned getting the scenario of suspended particle material concentration and the and the elemental chemical characterization of the atmospheric air of Uberlândia. For PTS, the annual secondary standards of concentration, available in CONAMA 003/90 Resolution, were surpassed in the whole period of study. The primary standard were surpassed in 2004 and 2005. In the case of inhalable particles, the annual standard was surpassed in 2004. The international standards to the even more fine particles (MP2,5), was not surpassed in none of the occasions in the period of July/06 to June/07. In order to analyse the temporal behaviour of the particle material MP10 and PTS, one used semivariogram models in determining the reach of temporal dependence among data and models of temporal series were used to estimate values of the PTS and MP10 concentration variables in the period from January to June/2007. In the study of series decomposition, one realized the presence of sazonal and of tendency components. Among the temporal series models studied, the one which better represented the behaviour of the series, as for the PTS as for the MP10, was the SARIMA model. The MP10 s filters were analysed by a thermal plasma, induced with optical emission spectrometry (ICP-OES), and the elements which pointed out were Al, Ca, K, Zn and S. The re-suspension of the soil, the vehicular and industry pollution are generating sources of these chemical elements and are part of the region studied. One also made a multivaried analyses of composition data using the technique of the main components, and two of the main components explained the results in more than 86%.